World War II : from the rise of the Nazi Party to the dropping of the atomic bomb - Taylor, Diane C. (Inquire and investigate great events of the twentieth century., 2018)
Explores the causes, events, key figures, and aftermath of World War II. Also discusses its legacies that impact the world today. Includes a timeline, a glossary, color illustrations, discussion questions, sidebars, primary sources, and links to online sources.